Functionalized Nanoporous Silica for the Removal of Heavy Metals from Biological Systems: Adsorption and Application - Yantasee, Wassana (2010)
Surface-functionalized nanoporous silica, often referred to as self-assembled monolayers on mesoporous supports (SAMMS), has previously demonstrated the ability to serve as very effective heavy metal sorbents in a range of aquatic and environmental systems, suggesting that they may be advantageously utilized for biomedical applications such as chelation therapy. Herein we evaluate surface chemistries for heavy metal capture from biological fluids, various facets of the materials’ biocompatibility, and the suitability of these materials as potential therapeutics. Of the materials tested, thiol-functionalized SAMMS proved most capable of removing selected heavy metals from biological solutions (i.e., blood, urine, etc.) Consequentially, thiol-functionalized SAMMS was further analyzed to assess the material’s performance under a number of different biologically relevant conditions (i.e., variable pH and ionic strength) to gauge any potentially negative effects resulting from interaction with the sorbent, such as cellular toxicity or the removal of essential minerals. Additionally, cellular uptake studies demonstrated no cell membrane permeation by the silica-based materials generally highlighting their ability to remain cellularly inert and thus nontoxic. The results show that organic ligand functionalized nanoporous silica could be a valuable material for a range of detoxification therapies and potentially other biomedical applications.